Mesozoic/cenozoic strike-slip tectonics in the catarinense shield and its correlation with structures associated with the continental rift in southeastern Brazil - MACHADO,RÔMULO (2022)
Abstract Structural studies carried out on mesoscopic scale of planar and linear brittle structures from quarries in Precambrian rocks of the central-southern portion of the Catarinense Shield led to a characterization of four main fault directions: NE-SW, NW-SE and some around N-S and E-W. The older dextral (~ N-S) and sinistral (~ E-W) strike-slip faults are explained through a paleostress field approximately NE-SW oriented. The younger dextral (NE-SW) and sinistral (NW) strike-slip faults are compatible with an approximately E-W oriented paleostress field. The oldest event fits between the Cretaceous and Cenozoic and the younger event fits between the Neogene and Quaternary.